Dimethyl malonate/LHMDS system as a new protocol for generating methyl formate anion (−COOMe) in the condensed-phase. Issue 15 (13th April 2016) - Di Bussolo, Valeria; Princiotto, Salvatore; Martinelli, Elisa; Bordoni, Vittorio; Crotti, Paolo
Graphical abstract: Highlights: A new protocol for the formation of methyl formate anion in the condensed-phase is given. The protocol is based on the treatment of dimethyl malonate with LHMDS. A rationalization based on a double deprotonation of dimethyl malonate is proposed. Abstract: The treatment of dimethyl malonate with LHMDS in anhydrous THF (condensed-phase) generates, in addition to the expected corresponding lithium enolate, methyl formate anion (or methoxycarbonyl anion, − COOMe) which can react with several electrophiles to give corresponding methoxycarbonyl derivatives by nucleophilic substitution reaction.